CULTURA POPULAR E PODER POLÍTICO NO MARANHÃO: contradições e tensões do bumba-meu-boi no governo Roseana Sarney - Silva, Gisélia Castro (2008)
Study of the political relationship established in connection with Maranhão s popular culture, focusing on bumba-meu-boi and Roseana Sarney s government (1995- 2002). The goal is to analyze, in the class relationship context of the contemporary capitalist State, how the government promotes a mutual dependence relationship with the popular culture groups in the sense of maintaining the political domination and the social order. The premise originates from the understanding that the period analyzed is marked by the institutionalization of feasts that comprise the popular culture universe, such as the June feasts, on the one hand, representing a political appropriation process of the cultural manifestations that comprise the popular imagination, and on the other hand, evidencing the contradictions and tensions of the political and marketing uses that this type of practice causes.